The Effect of Watching Elio Movie on Improving Vocabulary of Students at IPB Cirebon - Dewi Rahmah Aulia dewi; Afni Amaliyah; Dominggus Aji Pangestu Manek; Cici Situmorang (Journal of Innovative and Creativity, 2026)
This study focuses on examining the use of animated film Elio as a medium for learning English vocabulary particularly nouns, among students of IPB Cirebon. A descriptive qualitative research approach was employed, with data collected through vocabulary note sheets and semi-structured interviews. The data were obtained from students who watched film Elio with English subtitles. The findings indicate that the animated film Elio assists students in discovering new vocabulary, understanding the meanings of nouns through visual context and dialogue, and enhancing vocabulary retention. Visual elements and Englis subtitles play an important role in supporting vocabulary noticing and comprehension. Furthermore, students employ various vocabulary learning strategies during viewing process, such as note-taking and inferring word meanings from context. In conclusion, the animated film Elio serves as an effective learning medium for improving English vocabulary mastery, particularly nouns, and provides contextual and impressive learning opportunities for student.